Catcalling as a Human Rights Violation: An Examination of Law and Regulation in Public Spaces - Antungo, Titin (Estudiante Law Journal, 2025)
This research aims to analyze the legal aspects and social implications of catcalling as a form of human rights violation, as well as identify shortcomings in existing regulations to protect victims from verbal harassment in public spaces. The method used is a qualitative approach through the analysis of legal documents, literature review, and case studies of catcalling incidents in several major cities, which allows researchers to explore in-depth the public perception, cultural norms, and the application of laws related to sexual harassment. The research examines laws and regulations governing harassment and discrimination, comparing Indonesia's legal protection mechanisms with practices in other countries, to highlight weaknesses and opportunities for improvement in the national legal system. The results show that catcalling is a manifestation of human rights violations that undermine dignity, safety and gender equality, as the practice not only inflicts psychological trauma on victims, but also creates an atmosphere of insecurity in public spaces. The findings also indicate that while there is a legal framework on sexual harassment, its implementation and enforcement remain weak, influenced by social norms and gender stereotypes that consider such behavior as normal. Therefore, this study recommends reviewing existing regulations, raising public awareness through education, and implementing stricter legal sanctions, as strategic steps to address catcalling and realize an inclusive and safe social environment for all citizens